Cabaran pelaksanaan program pembangunan masyarakat setempat - Alias, Mohd. Azhar (2019)
The purpose of this research is to review the implementation of one of the home aid programs implemented by the government through the Ministry of Rural Development called as PPMS. This program is a home aid program for rural poor who do not have their own homes or residences to live a comfortable life and thus achieve a well-being life. However, there are still some participants in PPMS were still living in disadvantages. This study will focus to strengthen the implementation of PPMS based on the combination of project components that are provided by the government, that include basic infrastructure and utilities, housing and social amenities, human capital development and economic projects to increase participants' income. PPMS Lembah Beriah in the district of Kerian had been chosen to be studied in this research. Data collection process is done using qualitative method through semi-structural interviews and the findings of these primary data are will be further explained in detail. In addition, secondary data is obtained through reports, journals and other publications related to the title of the study being used as a reference in the study. The findings show that respondents have raised issues and problems that caused the participants in the PPMS Lembah Beriah still living in poverty. Some improvement suggestions also being pointed out including providing human resource development modules as well as offering a periodic skills training to the participants in order to improve their living and gain more income. Participants should be prepared and willing to improve themselves first in order to improve their well-being, while the government must play an important role to helps the participants that still surrounded with poverty. Lastly, the findings of this study are important to the government to improve the policies related to home aid programme that must be relevant with the current needs.